They don't wear black tie - Hirszman, Leon, 1937-; Guarnieri, Gianfrancesco; Diniz, Carlos Alberto; Montenegro, Fernanda; Mendes, Bete, 1949-; New Yorker Films; Empresa Brasileira de Filmes (New York, N. Y. : New Yorker Films, 1983)
Warm, intimate, family drama that, in the filmmakers words, "deals with the most important of Brazil's problems, the question of democracy." It is the story of the Brazil of the 1980's -- the big cities, the industry, and the individuals who are fighting for social and economic improvement in their country.
VHS format.
Videocassette release of 1983 motion picture released by Embrafilme.
In Portugese ; English subtitles.
Director, Leon Hirszman ; story and screenplay, Gianfrancesco Guarnieri and Leon Hirszman ; Cinematography, Lauro Escorel ; music, Radamés Gnatalli, executive producer, Carlos Alberto Diniz.
Fernanda Montenegro, Gianfrancesco Guarnieri, Carlos Alberto Ricelli, Bete Mendes.
Keywords: Feature films